(3Sff CHj OGhOs - (3SdjeGf Hf GdCTYK Hf ESMGb Hf HTjQ GdGROj GdSLSJGfj, CHh OGhO,J (B275 (3g` s
(3ChdgG (B:s
(3CNHQfG GdMGce CMeO Hf YHO GdQMje GdESeGYjdi Yf CHj YKeGf Cfg Udi Nda GHf eSYhO GdeZQH abQC bd gh Gddg CMO s
(3BNQgG (B:s
(3bGd (B: (3jG QShd Gddg CQGjJ Uhe GdEKfjf hGdNejS ? bGd (B: (3ajg hdOJ hajg CfRd Ydi GdbQBf s
(3YdjgG SeGYGJ cKjQI CbOegG SfI (B389 (3hGdfSNI ai CLRGA MOjKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B122s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeMehOjI (B- (3HecJHI GdeOjfI GdefhQI GdYGeI(B((3MOjK (B39) s
(3JHUQI GdJQGLe(Bs
Keywords: (3GdMOjK h GdeUWdMs